Negotiating Cultures in Cyberspace: Participation Patterns and Problematics - Kenneth Reeder; Leah P. Macfadyen; Joerg Roche; Mackie Chase (Language Learning and Technology, 2004)
In this paper we report findings of a multidisciplinary study of online participation by culturally diverse participants in a distance adult education course offered in Canada and examine in detail three of the study's findings. First, we explore both the historical and cultural origins of "cyberculture values" as manifested in our findings, using the notions of explicit and implicit enforcement of those values and challenging the assumption that cyberspace is a culture free zone. Second, we examine the notion of cultural gaps between participants in the course and the potential consequences for online communication successes and difficulties. Third, the analysis describes variations in participation frequency as a function of broad cultural groupings in our data. We identify the need for additional research, primarily in the form of larger scale comparisons across cultural groups of patterns of participation and interaction, but also in the form of case studies that can be submitted to microanalyses of the form as well as the content of communicator's participation and interaction online.